MSM20/1 raw data of EM120 multibeam echosounder (bathymetry & beam time series) - Wolfram H Geissler; Tilmann Schwenk; Paul Wintersteller; Reimer Wilhelm Weinrebe (PANGAEA, 2019)
Bathymetry data was recorded during R/V MARIA S. MERIAN cruise MSM20/1 between 06.01.2012 and 15.01.2012 at the Walvis Ridge. The aim of the expedition was to investigate critical geologic parameters for continental break-up and plume processes offshore northern Namibia, like crustal thickness and structure of the underlying Earth extquotesingles mantle. Geophysical methods were utilized to visualize structures relating to fossil plume and/or deformation processes. Several broadband ocean-bottom seismometers were recovered from the seafloor to gather seismological data. Hydroacoustic work during MSM20/1 was carried out as part of the "floating university" in order to teach Master students the acquisition, processing and interpretation of hydroacoustic data, which was derived from different water depths (from upper slope down to the deep sea basin) and environments (slope, abyssal plain, Walvis-Ridge) by two KONGSBERG multibeam echosounders. CI Citation: Paul Wintersteller (seafloor-imaging@marum.de) as responsible party for bathymetry raw data ingest and approval. Description of the data source: During the MSM20/1 cruise, the hull-mounted KONGSBERG EM120 multibeam ecosounder (MBES) was utilized to perform bathymetric mapping. Two transducer arrays transmit acoustic signals of 11.25 to 12.6 kHz in successive emission-reception cycles. With 191 overlapping beams per ping in a 2° (TX) by 2° (RX) footprint, it can form a maximum beam width of 150° across track and 2° along track. For the MSM20-1 cruise, the coverage sector was set between 120° and 130°. On flat ground, the swath width can achieve 5.5 times the water depth. For further information on the system, consult https://www.km.kongsberg.com/. The position and depth of the water column is estimated for each sounding through the two-way-travel time, beam angle and ray bending due to refraction in the water column by sound speed variations. During the MSM20/1 cruise, eight sound velocity profiles (SVP) were taken, of which one profile was applied to the EM120 data. The EM120 was running simultaneously with the EM1002 and PARASOUND sub-bottom profiling system. Acquisition of EM120 data was limited to the transit only due to a crash caused by overvoltage, which could not be resolved throughout the cruise. Responsible person during this cruise / PI: Wilhelm Weinrebe (wweinrebe@ifm-geomar.de), Tilmann Schwenk (tschwenk@marum.de) & Paul Wintersteller (pwintersteller@marum.de) Chief Scientist: Wolfram Geissler (Wolfram.Geissler@awi.de) CR: https://www.tib.eu/en/searchid/awi%3Adoi~10.2312%252Fcr_msm20_1/ CSR: https://www2.bsh.de/aktdat/dod/fahrtergebnis/2012/20120062.htm A special thanks goes to the participants of the Floating University during MSM20/1: Gesa Barkawitz, Johanna Bruckmann, Eva Eibl, Milen Iliev, Janina Kammann, Sofia Kufner, Irena Schulten, Daniela Wolf, Timo Zander, Andre Vollmert, Monika Tangeni Emvula, Justina Nafje-Ovanhu Hamalwa